Shifts in the Information Interface Between Managers and Analysts - Rebecca A. Ranucci (American Business Review)
Managers navigate information asymmetries between their firm and investors in large part through securities analysts. This paper refines the model of securities analysts as information intermediaries by using shifts in the information environment to reveal how managerial behaviors impact the effectiveness of analysts as information intermediaries. Using the insurance industry as the research setting, this study offers evidence that analysts are less accurate in the years following Regulation Fair Disclosure (RegFD) as information asymmetries increased, but that negative effect moderated under the capital market scrutiny that followed the Global Financial Crisis (GFC). Risk averse managers exacerbated adverse effects on analyst accuracy after RegFD, but their conservative approach improved analyst accuracy after the GFC. More accessible managers tempered declines in analyst accuracy post-RegFD, but post-GFC accuracy deteriorated among this group. This research contributes to a deeper understanding of information dependencies at the interface between managers and analysts.